Historical Research in Religion: An Amplification - Fitzer, Joseph (Bulletin for the study of religion, 2023)
In The Archive, we republish an article that, in hindsight, may have been ahead of its time with its prescience. Our pull for this issue is a 1982 piece from Joseph Fitzer (1939-2017) where he gives his response to two essays, one by John F. Wilson and one by Catherine L. Albanese, on historical studies of religion. Fitzer posits that religious history should not be a separate phenomenon but included in general history. In Fitzer’s opinion religious history needs to shift from theological formalities in a humanistic and aesthetic direction. This was originally published in our predecessor publication, CSR Bulletin 13.4.